السر المهني في أداء الوظيفة العمومية بالجزائر - حاج لعروسي نادية. – بــوخلط كلثـوم (المسيلة, 2023)
يعد السر المهني التزام أساسي وهام يقع على عاتق الموظف، فوظيفته تقتضي عليه االطال على معلومات سرية تخص اإلدارة واألفراد. ويجب عليه كتمانها وعدم إفشائها، كونها تمس بالمبادئ األخالقية بالدرجة األولى وتحدث ضرر بالمصلحة العامة والمصلحة الخاصة بالدرجة الثانية، فكتمان السر المهني وافشائه خطر بحد ذاته، لذا أحاطه المشر الجزائري بحماية خاصة ووضع له أهمية بالغة له قواعد مميزة من خالل قانون الوظيفة العامة، حيث يعتبر كل فعل إفشاء لألسرار الوظيفية يصدر عن الموظف العمومي دون عذر شرعي خطأ تأديبي، فتقوم الجهة المختصة بالتأديب بمساءلته التـأديبية وفق إجراءات تأديبية كرسها القانون للوظيفة العامة. Summary: Professional secrecy is an essential and important commitment that falls on the employee. Their job requires them to have access to confidential information regarding management and individuals. It is imperative for them to keep this information confidential and not disclose it, as it primarily violates ethical principles and secondarily causes harm to the public and private interests. The importance of maintaining professional secrecy cannot be overstated, and its disclosure is inherently dangerous. Therefore, Algerian legislation has provided special protection and established specific rules for it through the Public Service Law. Any act of disclosing professional secrets by a public employee without a legitimate excuse is considered a disciplinary offense. The competent disciplinary authority is responsible for holding the employee accountable according to disciplinary procedures stipulated by the law for the public service
Keywords: السر المهني - أداء الوظيفة العمومية - الجزائر